A descriptive analysis of the seasonal patterns of bone stress injury incidence in Division I collegiate distance runners - Wolff, A.; Kurina, L. M.; Sainani, K. L.; Tenforde, A. S.; Nattiv, A.; Fredericson, M. (The American Journal of Sports Medicine, 2025)
Background: A bone stress injury (BSI) is a common overuse injury in collegiate athletes, particularly cross-country and track and field runners. Limited work describes the seasonality of BSIs or the differences in rates and anatomic locations of BSIs in collegiate runners.